Evaluasi Model PBL dalam Meningkatkan Berpikir Kritis Siswa pada Pelajaran PAI SDN 04 Batu Putih - Erwina, Meifa Adinda; Remiswal, Remiswal; Khadijah, Khadijah (YASIN, 2025)
This study is motivated by the low critical thinking skills of students in Islamic Education (Pendidikan Agama Islam, PAI) learning at SDN 04 Batu Putih, which remains dominated by lecture-based and rote memorization methods, thus limiting students' active and analytical participation. The objective of this research is to evaluate the effectiveness of the Problem Based Learning (PBL) model in enhancing students' critical thinking skills. The study employs a quantitative approach with a pre-experimental design of the one-group pretest-posttest type. The research sample consisted of 30 fifth-grade students selected through purposive sampling. The instrument used was a critical thinking skills test, analyzed descriptively and inferentially using a paired sample t-test. The results show an increase in the average critical thinking score from 64.4 on the pretest to 76.9 on the posttest, with a gain of 12.5 points. The t-test yielded a t-value of 11.24 with a significance level of p < 0.05, indicating a significant improvement. Additionally, the posttest score distribution shifted to a higher category, with the majority of students scoring above 74. In conclusion, the implementation of PBL is proven effective in improving students' critical thinking abilities and contextual understanding of PAI material. The implication is that PBL should be applied more broadly and continuously in PAI instruction to foster active and meaningful learning environments. It is recommended that teachers attend PBL implementation training and manage instructional time effectively to optimize the learning process. Further research is suggested to explore the impact of PBL on character development and other learning outcomes.